A novel microRNA promotes coxsackievirus B4 infection of pancreatic β cells - Lalani, Salima; Knudsen, Joseph; Kenney, James; Hober, Didier; DiPersio, C. Michael; Gerber, Allen (Frontiers in Immunology, 2024)
The epidemiological association of coxsackievirus B infection with type 1 diabetes suggests that therapeutic strategies that reduce viral load could delay or prevent disease onset. Moreover, recent studies suggest that treatment with antiviral agents against coxsackievirus B may help preserve insulin levels in type 1 diabetic patients. In the current study, we performed small RNA-sequencing to show that infection of immortalized trophoblast cells with coxsackievirus caused differential regulation of several miRNAs. One of these, hsa-miR-AMC1, was similarly upregulated in human pancreatic β cells infected with coxsackievirus B4. Moreover, treatment of β cells with non-cytotoxic concentrations of an antagomir that targets hsa-miR-AMC1 led to decreased CVB4 infection, suggesting a positive feedback loop wherein this microRNA further promotes viral infection. Interestingly, some predicted target genes of hsa-miR-AMC1 are shared with hsa-miR-184, a microRNA that is known to suppress genes that regulate insulin production in pancreatic β cells. Consistently, treatment of coxsackievirus B4-infected β cells with the hsa-miR-AMC1 antagomir was associated with a trend toward increased insulin production. Taken together, our findings implicate novel hsa-miR-AMC1 as a potential early biomarker of coxsackievirus B4-induced type 1 diabetes and suggest that inhibiting hsa-miR-AMC1 may provide therapeutic benefit to type 1 diabetes patients. Our findings also support the use of trophoblast cells as a model for identifying microRNAs that might be useful diagnostic markers or therapeutic targets for coxsackievirus B-induced type 1 diabetes.